LabVIEW implementation of chaotic masking with adaptively synchronised forced Van der Pol oscillators and its application in real-time image encryption. (2017) - Vaidyanathan, Sundarapandian; Rajagopal, Karthikeyan
Chaotic oscillators find many applications in the field of cryptography and secure communication engineering. This paper first details one such approach of applying a forced Van der Pol chaotic oscillator and its synchronised slave model in chaotic masking and image encryption. This approach applies the chaotic masking to the secondary image and thus changing the image pixels and the masked image is used for encoding the original image. We have developed a real-time image encryption algorithm by capturing pictures through the NI IMAQdx tools. The proposed model is implemented in LabVIEW and experimentally verified for the efficiency of the encryption algorithm.